2020
DOI: 10.3390/ijerph17041413
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Clustering Characteristics of Tuberculosis in Khyber Pakhtunkhwa Province, Pakistan, 2015–2019

Abstract: The number of tuberculosis (TB) cases in Pakistan ranks fifth in the world. The National TB Control Program (NTP) has recently reported more than 462,920 TB patients in Khyber Pakhtunkhwa province, Pakistan from 2002 to 2017. This study aims to identify spatial and space-time clusters of TB cases in Khyber Pakhtunkhwa province Pakistan during 2015–2019 to design effective interventions. The spatial and space-time cluster analyses were conducted at the district-level based on the reported TB cases from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These countries are main sources of TB, which affect TB transmission in Iran [ 18 ]. A spatio-temporal study of TB in Pakistan [ 32 ] revealed northern and western parts of country as high-risk clusters for TB. Western areas of this country share long borders with eastern and south-eastern Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These countries are main sources of TB, which affect TB transmission in Iran [ 18 ]. A spatio-temporal study of TB in Pakistan [ 32 ] revealed northern and western parts of country as high-risk clusters for TB. Western areas of this country share long borders with eastern and south-eastern Iran.…”
Section: Discussionmentioning
confidence: 99%
“…A TB study in Pakistan [ 32 ] conducted by spatial scan statistics identified spatio-temporal clustering with high-risk clusters across the country during 2015–2019, particularly in the northern and western parts of the study area. Another study, assessing spatial and temporal pattern of TB in the 75 municipalities in the Northeast of Brazil during 2001 to 2016 by empirical Bayesian and Moran statistic [ 23 ], noted an increased trend of TB in patients under 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…One of the statistical methods for detecting spatial/geographical clusters of a disease is the Spatial Scan Statistic (Kulldorff, 1997), which is a freely available software called SaTScan™ (https://www.satscan.org/). It is widely used in public health and epidemiology (Amin et al, 2019;Omodior et al, 2019;Souza et al, 2019;Amin & Rivera, 2020;Desjardins et al, 2020;Ullah et al, 2020). There are several other cluster analysis algorithms in the literature, such as DBSCAN (Ester et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…All study sites were linked to a mental health facility for patient referral. As the first point of contact, the DOTS facilitator conducted the initial screening using the two-item Patient Health Questionnaire-2 (PHQ-2) by Kroenke et al 24 Patients with a score of 2 or less entered the facility's usual care pathway, whereas those with a score of more than 2 were further screened using the nine-item Patient Health Questionnaire-9 (PHQ-9) by Kroenke et al 25 Patients were further managed based on their PHQ-9 screening scores: no depression (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27) (Figure 1).…”
Section: Care Pathwaymentioning
confidence: 99%